2003
DOI: 10.1056/nejmoa030847
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Wnt-Signaling Antagonist DKK1 in the Development of Osteolytic Lesions in Multiple Myeloma

Abstract: The production of DKK1, an inhibitor of osteoblast differentiation, by myeloma cells is associated with the presence of lytic bone lesions in patients with multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
1,031
2
20

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,377 publications
(1,091 citation statements)
references
References 38 publications
38
1,031
2
20
Order By: Relevance
“…DKK1 was initially identified as an inhibitor of WNT-induced axis duplication in Xenopus development (Glinka et al, 1998). Subsequent studies implicated DKK1 in the pathogenesis of osteolytic lesions in patients with multiple myeloma (Tian et al, 2003). During our study, Hall et al (2005) reported that PC-3 prostate cancer cells express DKK1 and showed by genetic manipulation of DKK1 in C4-2b prostate cancer cells that WNT signaling participates in prostate cancerinduced new bone formation.…”
Section: Discussionmentioning
confidence: 62%
“…DKK1 was initially identified as an inhibitor of WNT-induced axis duplication in Xenopus development (Glinka et al, 1998). Subsequent studies implicated DKK1 in the pathogenesis of osteolytic lesions in patients with multiple myeloma (Tian et al, 2003). During our study, Hall et al (2005) reported that PC-3 prostate cancer cells express DKK1 and showed by genetic manipulation of DKK1 in C4-2b prostate cancer cells that WNT signaling participates in prostate cancerinduced new bone formation.…”
Section: Discussionmentioning
confidence: 62%
“…Over-expression of Dkk1 in bone marrow aspirates from patients with multiple myeloma was initially identified by cDNA microarray. Dkk1 concentrations were increased in bone marrow plasma and peripheral blood of patients with multiple myeloma, as compared to healthy individuals or to patients with MGUS (56). In addition, osteoblast differentiation was blocked by bone marrow serum from patients with myeloma, and the inhibitory effect was found to be the result of Dkk1 in the serum.…”
Section: Inhibition Of Wnt Signalingmentioning
confidence: 90%
“…Recent evidence suggests a role for each of these classes of inhibitors in the development of myeloma bone disease. The soluble, extracellular antagonist of the Wnt signaling pathway, Dkk-1, has been identified as a potential mediator of osteoblast dysfunction in myeloma bone disease (56). Dkk1 is expressed by osteoblasts and bone marrow stromal cells, and has been demonstrated to inhibit bone formation in osteoblasts in vitro (57).…”
Section: Inhibition Of Wnt Signalingmentioning
confidence: 99%
“…Examples include multiple myeloma (Tian et al, 2003) and some forms of prostate cancer (Hall et al, 2005). Damage of the bone by malignancy can increase the severity of the disease by providing a permissive microenvironment for tumour growth and metastatic events.…”
mentioning
confidence: 99%
“…Damage of the bone by malignancy can increase the severity of the disease by providing a permissive microenvironment for tumour growth and metastatic events. In multiple myeloma, Dkk-1 is readily detectable in the blood of individuals in the later stages of the disease who have characteristic osteolytic bone lesions (Tian et al, 2003).…”
mentioning
confidence: 99%